Academic business librarians' assistance to community entrepreneurs. Issue 1 (2014) - Louise Mort Feldmann
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper was to examine on a national scale how academic business librarians are working with community organizations and other libraries to assist local entrepreneurs with their information needs. Design/methodology/approach – A multi method approach was used to gather information. In spring 2012, a survey and follow‐up interviews were conducted with academic business librarians. Additionally, business consultants who have worked with librarians were interviewed. Findings – The survey had 53 respondents. Of those, 40 percent indicated that they collaborate to assist entrepreneurs. Five interviewees confirmed the findings of the survey and discussed their collaborative arrangements. The consultants discussed best practices in working with entrepreneurs. Research limitations/implications – This research studied academic business librarians and reached those who monitor the buslib‐l and brass‐l listservs. Not all librarians have the time or take the time to respond to a survey. Additionally, this research only explored collaborations to assist local entrepreneurs and did not specifically focus on campus entrepreneurs and outreach to business schools. Practical implications – This study provides information on academic business librarians' efforts to assist community entrepreneurs. It also provides some information on lessons learned. Originality/value – A national study of academic business librarians' outreach to entrepreneurs has not been conducted in the past. <ack> <x xml:space="preserve"> Acknowledgements </x> This research project was funded in part by an Emerald Business Research Grant Award. Initial findings were presented in a poster session at the Colorado Association of Libraries Conference, October 2012, in Keystone, Colorado. The author wishes to thank Christine Hamilton‐Pennell, Kelly Peters, and Anne MacDonald for their inspiration for this research, and especially for their enthusiasm in helping entrepreneurs and for supporting and acknowledging the role of both academic and public librarians in this assistance. Also, the author wishes to thank the academic business librarians who assisted with this research via their survey and interview participation. </ack>